2006
DOI: 10.1111/j.1365-2745.2006.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term effects of changes in reindeer grazing pressure on tundra heath vegetation

Abstract: Summary1 Previous studies of plant-herbivore interactions have typically focused either on short-term or long-term effects. By directly comparing effects at different temporal scales, I studied whether short-term experiments provide good indications of the long-term effects of herbivory. 2 I reciprocally transplanted turfs of tundra heath vegetation within areas covered by a long-term (40 years) reindeer manipulation experiment, in order to examine the effects of all possible permutations of light, moderate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
103
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 38 publications
8
103
3
Order By: Relevance
“…Vistnes and Nellemann [65] also conclude that heavy grazing may be beneficial to a range of colonizing species in the short term, while in the long term the vegetation cover might be destroyed by erosion. However, this is not supported by Olofsson [66] who reports that the short-term effects from increase in reindeer grazing can give good indications of most of the long-term effects on species richness.…”
Section: Alternative Explanations To Observed Vegetation Changesmentioning
confidence: 45%
See 1 more Smart Citation
“…Vistnes and Nellemann [65] also conclude that heavy grazing may be beneficial to a range of colonizing species in the short term, while in the long term the vegetation cover might be destroyed by erosion. However, this is not supported by Olofsson [66] who reports that the short-term effects from increase in reindeer grazing can give good indications of most of the long-term effects on species richness.…”
Section: Alternative Explanations To Observed Vegetation Changesmentioning
confidence: 45%
“…Exclusion of grazing reindeer has been shown to lead to an increase in cover for Betula nana, as well as an increase in the cover of dwarf shrubs, forbs and grasses [67]. Dwarf shrub dominated vegetation on tundra heaths in areas with light grazing pressure from reindeer will often rapidly change into grasslands when the grazing pressure increased [66]. The cover of Betula nana has been shown to increase under moderate grazing of sheep but decrease under a high grazing pressure [68].…”
Section: Alternative Explanations To Observed Vegetation Changesmentioning
confidence: 99%
“…Plant diversity does not, however, always change in response to grazing; particularly, when environmental variation has more impact on vegetation composition than grazing (Stohlgren, Schell & Vanden Heuvel 1999). Furthermore, the response rates of plant communities to increased and decreased herbivory may not be symmetric, with a slower response observed when herbivory is decreased than increased (Olofsson 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A transplantation study between high and low reindeer density areas showed that the heath vegetation can change into graminoid-dominated vegetation in just a few years, although such graminoid-dominated vegetation is fairly stable even in the absence of active grazing during the first decade after herbivore removal. This was interpreted as a priority effect linked to the dense grass swards being hard to invade (Olofsson 2006). However, like many other systems where strong historical contingency, priority effects and alternative stable states are discussed (Fukami 2015), and knowledge of conditions that deliver such effects, as well as empirical data on the stability of states, are lacking (Beisner and others 2003).…”
Section: Introductionmentioning
confidence: 99%